A Multicomponent Behavioral Intervention to Reduce Stroke Risk Factor Behaviors. Issue 10 (October 2015) - Brown, Devin L.; Conley, Kathleen M.; Sánchez, Brisa N.; Resnicow, Kenneth; Cowdery, Joan E.; Sais, Emma; Murphy, Jillian; Skolarus, Lesli E.; Lisabeth, Lynda D.; Morgenstern, Lewis B.
<x xml:space="preserve">Abstract</x> Background and Purpose— The Stroke Health and Risk Education Project was a cluster-randomized, faith-based, culturally sensitive, theory-based multicomponent behavioral intervention trial to reduce key stroke risk factor behaviors in Hispanics/Latinos and European Americans. Methods— Ten Catholic churches were randomized to intervention or control group. The intervention group received a 1-year multicomponent intervention (with poor adherence) that included self-help materials, tailored newsletters, and motivational interviewing counseling calls. Multilevel modeling, accounting for clustering within subject pairs and parishes, was used to test treatment differences in the average change since baseline (ascertained at 6 and 12 months) in dietary sodium, fruit and vegetable intake, and physical activity, measured using standardized questionnaires. A priori, the trial was considered successful if any one of the 3 outcomes was significant at the 0.05/3 level. Results— Of 801 subjects who consented, 760 completed baseline data assessments, and of these, 86% completed at least one outcome assessment. The median age was 53 years; 84% subjects were Hispanic/Latino; and 64% subjects were women. The intervention group had a greater increase in fruit and vegetable intake than the control group (0.25 cups per day [95% confidence interval: 0.08, 0.42], P=0.002), a greater decrease in sodium intake (−123.17 mg/d [−194.76, −51.59], P=0.04), but no difference in change in moderate- or greater-intensity physical activity (−27 metabolic equivalent–minutes per week [−526, 471], P=0.56). Conclusions— This multicomponent behavioral intervention targeting stroke risk factors in predominantly Hispanics/Latinos was effective in increasing fruit and vegetable intake, reaching its primary end point. The intervention also seemed to lower sodium intake. Church-based health promotions can be successful in primary stroke prevention efforts. Clinical Trial Registration— URL: http://www.clinicaltrials.gov. Unique identifier: NCT01378780.